2015
DOI: 10.1371/journal.pone.0135955
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Site Knowledge Attitude and Practice Survey of Ebola Virus Disease in Nigeria

Abstract: BackgroundThe 2014 Ebola Virus Disease (EVD) outbreak was characterised by fear, misconceptions and irrational behaviours. We conducted a knowledge attitude and practice survey of EVD in Nigeria to inform implementation of effective control measures.MethodsBetween July 30th and September 30th 2014, we undertook a cross sectional study on knowledge, attitude and practice (KAP) of Ebola Virus Disease (EVD) among adults of the general population and healthcare workers (HCW) in three states of Nigeria, namely Baye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 13 publications
6
78
2
1
Order By: Relevance
“…The level of public knowledge regarding to EVD in this study is lower compared to other studies in the countries where the EVD epidemic took places such as in Nigeria [15,16] and in Liberia [17]. The studies in Nigeria reported that 43.1% and 45.4% of the participants had satisfactory knowledge of EVD transmission and preventive measures [15].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The level of public knowledge regarding to EVD in this study is lower compared to other studies in the countries where the EVD epidemic took places such as in Nigeria [15,16] and in Liberia [17]. The studies in Nigeria reported that 43.1% and 45.4% of the participants had satisfactory knowledge of EVD transmission and preventive measures [15].…”
Section: Discussioncontrasting
confidence: 66%
“…Previous study also found that education level was associated with a better knowledge regarding to EVD [15]. However, another study found that education was not associated with knowledge regarding to EVD [16]. Taking together, it seems that education is a cofounding factor for knowledge regarding to EVD.…”
Section: Discussionmentioning
confidence: 83%
“…Ebola-related KAP assessments were conducted in Sierra Leone ( 4 ), Liberia ( 5 ), Nigeria ( 6 ), and in one region in Guinea ( 7 ) during Ebola epidemics in 2014–2015. To learn more about Ebola-related KAP in Guinea as the nation’s epidemic waned following more than a year of Ebola education and prevention activities, several organizations conducted an Ebola KAP assessment across all administrative regions in August 2015.…”
mentioning
confidence: 99%
“…Education has been found to influence people's knowledge about EVD in Nigeria (9). In Uganda being educated beyond primary level was a significant predictor of awareness towards EVD and Marburg (10).…”
Section: Discussionmentioning
confidence: 94%